2021
DOI: 10.1159/000521163
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Weight and Alcohol Consumption on Hyperuricemia and Their Population Attributable Fractions: A National Health Survey in China

Abstract: Introduction: The prevalence of hyperuricemia is increasing world widely; the understanding of population attributable faction of modifiable risk factors is important for disease prevention. Given the sparse evidence on how modifiable risk factors influence hyperuricemia in mainland China, we aim to explore the effect of excess weight and alcohol consumption and the population attributable fractions of hyperuricemia based on a national survey in mainland China. Methods: Using data from China National Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…The final sample was 31,746, restricted to subjects without missing values of SUA, BMI or %BF, and eGFR ≥ 60 ml/min per 1.73 m 2 [to exclude potential kidney disorders ( 17 )], no self-reported as gout or using diuretic medication. The flowchart of the inclusion and exclusion criteria for the analytical sample was illustrated in our previous work ( 18 ). As SUA varies substantially by sex, we analyzed the data by sex separately.…”
Section: Methodsmentioning
confidence: 99%
“…The final sample was 31,746, restricted to subjects without missing values of SUA, BMI or %BF, and eGFR ≥ 60 ml/min per 1.73 m 2 [to exclude potential kidney disorders ( 17 )], no self-reported as gout or using diuretic medication. The flowchart of the inclusion and exclusion criteria for the analytical sample was illustrated in our previous work ( 18 ). As SUA varies substantially by sex, we analyzed the data by sex separately.…”
Section: Methodsmentioning
confidence: 99%
“…About 70% of daily SUA excretion occurs via the kidney, and in 5%-25% of humans, impaired renal excretion leads to hyperuricemia (5). Our previous work revealed an around 20% hyperuricemia prevalence among adults in mainland China (6). Hyperuricemia is a necessary precursor to develop gout and is also associated with an increased risk of cardiometabolic morbidities and premature mortality (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work revealed that, in men, the prevalence of overweight/obesity and current alcohol drinking was high, that is, over 40 and 65%, respectively. The proportions of HUA cases that could be attributed to overweight/obesity and alcohol consumption were 20.6 and 12.8%, respectively ( 4 ). It is well known that excess adiposity and alcohol consumption are the most essential modifiable risk factors for cardiometabolic diseases, and previous studies have explored their interaction role toward metabolic health ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work indicated that over 65% of men were obese, whereas 32% were women due to their much less alcohol drinking behaviors as well as lower alcohol intake dose than men ( 4 ). The combined effect of excess adiposity and alcohol consumption, thereby, may be more essential for the male population from the public health prospective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation